2013
DOI: 10.1021/jm301856j
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bacteriostatic DNA Aptamers for Salmonella

Abstract: Salmonella is one of the most dangerous and common food-borne pathogens. The overuse of antibiotics for disease prevention has led to the development of multidrug resistant Salmonella. Now, more than ever, there is a need for new antimicrobial drugs to combat these resistant bacteria. Aptamers have grown in popularity since their discovery, and their properties make them attractive candidates for therapeutic use. In this work, we describe the selection of highly specific DNA aptamers to S. enteritidis and S. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 22 publications
0
38
0
2
Order By: Relevance
“…They used SPR (Surface Plasmon Resonance) assay to detect binding between Troponin I protein and aptamer and perhaps because, we used a full length aptamer which was flanked by both primer sequences, whereas Mamoru Hyodo and coworkers found that only some of nucleotides were responsible for binding (Ara et al, 2012), also in a study by Zamay, all truncated aptamers showed better binding abilities to target, indicating that primer sites do not participate in binding recognition. This is likely the result of decreased negative charge and steric hindrance of the aptamer caused by the removal of the primer binding portion (Kolovskaya et al, 2013). Lin-Yue believes that the stem loop modification of aptamer can be useful in identifying target domains, getting rid of excessive unnecessary nucleotides (Kaur and Yung, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They used SPR (Surface Plasmon Resonance) assay to detect binding between Troponin I protein and aptamer and perhaps because, we used a full length aptamer which was flanked by both primer sequences, whereas Mamoru Hyodo and coworkers found that only some of nucleotides were responsible for binding (Ara et al, 2012), also in a study by Zamay, all truncated aptamers showed better binding abilities to target, indicating that primer sites do not participate in binding recognition. This is likely the result of decreased negative charge and steric hindrance of the aptamer caused by the removal of the primer binding portion (Kolovskaya et al, 2013). Lin-Yue believes that the stem loop modification of aptamer can be useful in identifying target domains, getting rid of excessive unnecessary nucleotides (Kaur and Yung, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…LOD is 25 CFU/ml in bacterial suspension.Duan et al (2013a)   S. typhimurium whole   live cellsDNAImpedimetric aptasensor. LOD is 600 CFU/ml in bacterial suspension.Labib et al (2012b) and Kolovskaya et al (2013)   S. enteritidis whole   live cellsDNAImpedimetric biosensor. LOD is 600 CFU/ml in bacterial suspension.Labib et al (2012a)  Lateral flow aptasensor.…”
Section: Antiviral Aptamersmentioning
confidence: 99%
“…Whole bacterium cells were also used by Berezovski and co-workers for the selection of DNA aptamers against S. enterica serotype Typhimurium and S. enterica serotype Enteritidis (Kolovskaya et al, 2013; Labib et al, 2012b). A mixture of aptamers selected against S. typhimurium inhibited the growth of the bacteria on Petri dishes, and the STYP-3 aptamer with the highest binding affinity ( K d  = 25 nM) was applied for the development of an impedimetric biosensor.…”
Section: Antibacterial Aptamersmentioning
confidence: 99%
“…DNA aptamers, capable of binding and inhibiting bacterial tubercle infection, have also been described (Xiaolian & Fan 2008), as well as aptamers against cytolysin toxin of enterococci (Morrissey & Haeberli 2003), Bacillus cereus and Salmonella (Kolovskaya et al 2013). However, the prohibitive cost of aptamers in comparison to traditional antibiotics limits their applicability in this field, except where antibiotic resistance or lack of adequate antibiotics make them the preferred choice.…”
Section: Aptamers In Bacterial Diagnosismentioning
confidence: 99%